In Vitro Osteocompatibility and Enhanced Biocorrosion Resistance of Diammonium Hydrogen Phosphate-Pretreated/Poly(ether imide) Coatings on Magnesium for Orthopedic Application - Yang, Yuyun; Zhou, Juncen; Chen, Qiang; Detsch, Rainer; Cui, Xiufang; Jin, Guo; Virtanen, Sannakaisa; Boccaccini, Aldo R. (ACS Applied Materials and Interfaces, 2019)
Magnesium, as a biodegradable metal, is a promising candidate for biomedical applications. To modify the degradation behavior of magnesium and improve its osteocompatibility, chemical conversion and spin coating methods were combined to develop a diammonium hydrogen phosphate-pretreated/poly(ether imide) (DAHP/PEI) co-coating system. The diammonium hydrogen phosphate pretreatment was employed to enhance the attachment between PEI coatings and the magnesium substrate; meanwhile, it could serve as another bioactive and anticorrosion layer when PEI coatings break down. Surface characterization, electrochemical tests, and short-term immersion tests in DMEM were performed to evaluate DAHP/PEI coatings. Electrochemical measurements showed that DAHP/PEI coatings significantly improved the corrosion resistance of pure magnesium. No obvious changes of the chemical compositions of DAHP/PEI coatings occurred after 72 h of immersion in DMEM. An in vitro cytocompatibility study confirmed that viability and LDH activity of human osteoblast-like cells on DAHP/PEI coatings showed higher values than those on the DAHP-pretreated layer and pure magnesium. The DAHP-pretreated layer could still enhance the ALP activity of MG-63 cells after the degradation of PEI in DAHP/PEI coatings. Besides that, the in vitro cellular response to the treated magnesium was investigated to gain knowledge on the differentiation and proliferation of human adipose-derived stem cells (hADSCs). Cell distribution and morphology were observed by fluorescence and SEM images, which demonstrated that DAHP/PEI coatings facilitated cell differentiation and proliferation. The high level of C-terminals of collagen type I production of hADSCs on DAHP/PEI coatings indicated the potential of the coating for promoting osteogenic differentiation. Positive results from long-term cytocompatibility and proliferation tests indicate that DAHP/PEI coatings can offer an excellent surface for hADSCs.
CRIS-Team Scopus Importer:2019-08-27
Keywords: coatings; corrosion; cytocompatibility; diammonium hydrogen phosphate; magnesium; osteocompatibility; poly(ether imide); stem cells